2005
DOI: 10.1016/j.clpt.2005.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic organic anion transporting polypeptide 1B1 is a major determinant of repaglinide pharmacokinetics

Abstract: Genetic polymorphism in SLCO1B1 is a major determinant of interindividual variability in the pharmacokinetics of repaglinide. The effect of SLCO1B1 polymorphism on the pharmacokinetics of repaglinide may be clinically important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
268
3
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(288 citation statements)
references
References 39 publications
16
268
3
1
Order By: Relevance
“…Initial in vitro studies for CYP2C8*3 suggested a lower activity, 31,32 but more recent studies in healthy volunteers have repeatedly demonstrated an increased metabolizing capacity for this allele. [33][34][35][36] In contrast, CYP2C8 haplotype C 35,41 and CYP3A5*3 37 confer a reduced activity. As the polymorphisms conferring a low metabolizing capacity were associated with protection, whereas the allele with increased activity showed a higher neurotoxicity (Figure 2), and the effects of these polymorphisms were independent, we incorporated them in a single prediction model (risk alleles: rs11572080 A, rs1113129 G and rs776746 G; Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial in vitro studies for CYP2C8*3 suggested a lower activity, 31,32 but more recent studies in healthy volunteers have repeatedly demonstrated an increased metabolizing capacity for this allele. [33][34][35][36] In contrast, CYP2C8 haplotype C 35,41 and CYP3A5*3 37 confer a reduced activity. As the polymorphisms conferring a low metabolizing capacity were associated with protection, whereas the allele with increased activity showed a higher neurotoxicity (Figure 2), and the effects of these polymorphisms were independent, we incorporated them in a single prediction model (risk alleles: rs11572080 A, rs1113129 G and rs776746 G; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…For CYP2C8 several studies have demonstrated that CYP2C8*3 (R139K; K399R) exhibits an altered activity. 31-36 CYP2C8*4 (I264M) has not been associated with an altered enzyme activity, 33 but it encodes a common variant protein which might not have been sufficiently studied. Regarding CYP2C8 haplotypes B and C, represented by CYP2C8*1B (rs7909236) and rs1113129, 25 we recently showed that they conferred an increased and reduced activity, respectively.…”
Section: Patientsmentioning
confidence: 99%
“…[4][5][6][7] Moreover, the 521C/C genotype has been associated with increased plasma concentrations of statins and glinides in human studies. [8][9][10] In SLCO1B3, several single-nucleotide polymorphisms (SNPs) have been identified in coding and noncoding regions. At least three nonsynonymous SNPs have been found so far, with 334T4G (S112A) and 699G4A (M233I) increasing transporter activity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, impaired function of OATP1B1 caused by genetic polymorphisms would greatly affect plasma concentrations of substrate drugs, which may result in decrease in efficacy of the drugs or in increase in the risk of development of adverse effects. For example, it has been reported that carriers of the single nucleotide polymorphism (SNP), c.521T4C (p.Val174Ala), OATP1B1*5 or *15, show increased plasma concentrations of pravastatin, 6-8 repaglinide 9 and simvastatin. 10 Severe toxicity after irinotecanbased chemotherapy for lung cancer has also been reported in a patient with a homozygote for the SLCO1B1*15 allele, which carries the SNP c.521T4C (p.Val174Ala).…”
Section: Introductionmentioning
confidence: 99%